2019
DOI: 10.1111/jdv.15419
|View full text |Cite
|
Sign up to set email alerts
|

Acne relapses: impact on quality of life and productivity

Abstract: Background Acne is a common skin disease that mostly affects teenagers, with a negative impact on quality of life. Recently, adult acne and acne relapses have increased in frequency, for yet unknown reasons. Objective This non‐interventional, real‐life study sought to investigate the rate of acne relapses and their impact on quality of life and productivity (loss/absenteeism) among teenagers and adults. Methods An online self‐administered que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 21 publications
2
54
1
5
Order By: Relevance
“…In terms of drug use characteristics, number of relapses, severe MAUD, and comorbidity with OUD negatively predicted at least one domain of QOL. First, more relapses predicted poorer PHYSQOL and SOCIALQOL, which was consistent with the findings of some recurrent diseases such as acne (53), depression (54) and SUDs (55). Our findings suggested that relapse was an important risk factor for QOL of SUDs patients, especially in their physical and social domains.…”
Section: Discussionsupporting
confidence: 85%
“…In terms of drug use characteristics, number of relapses, severe MAUD, and comorbidity with OUD negatively predicted at least one domain of QOL. First, more relapses predicted poorer PHYSQOL and SOCIALQOL, which was consistent with the findings of some recurrent diseases such as acne (53), depression (54) and SUDs (55). Our findings suggested that relapse was an important risk factor for QOL of SUDs patients, especially in their physical and social domains.…”
Section: Discussionsupporting
confidence: 85%
“…According to the study in China, 30.8% acne patients reported that acne had a negative impact on their quality of life (7). Several studies showed that people with acne had lower selfconfidence, the difficulty of making friends, challenges of going to school, and the trouble of finding a job (8,9). Moreover, acne patients have a higher propensity of underlying mental 1 Spironolactone is $350, oral antibiotics are $501, topical antibiotics are $920, topical retinoids are $1,805, topical combination antibiotics are $2,282, topical combination antibiotics and retinoids are $3,770, the median cost for isotretinoin in males and females are $3,227 and $3,806 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…According to the study in China, 30.8% acne patients reported that acne had a negative impact on their quality of life ( 7 ). Several studies showed that people with acne had lower self-confidence, the difficulty of making friends, challenges of going to school, and the trouble of finding a job ( 8 , 9 ). Moreover, acne patients have a higher propensity of underlying mental disorders, including anxiety, depression and suicide ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of acne is as high as 85%. Although it is not a life-threatening disease, it has a great psychological impact on patient's life (Dreno et al., 2019). Cutibacterium acnes ( C. acnes , formerly Propionibacterium acnes ) is the dominant pathogen bacterial to acne, which is an anaerobic Gram-positive Corynebacterium (Scharschmidt, 2019).…”
Section: Introductionmentioning
confidence: 99%